Comparative evaluation of simple indices using a single fasting blood sample to estimate beta cell function after islet transplantation. Issue 4 (21st January 2018) - Gołębiewska, Justyna E.; Solomina, Julia; Thomas, Celeste; Kijek, Mark R.; Bachul, Piotr J.; Basto, Lindsay; Gołąb, Karolina; Wang, Ling‐jia; Fillman, Natalie; Tibudan, Martin; Ciepły, Kamil; Philipson, Louis; et al.
Abstract : Six single fasting blood sample–based indices—Secretory Unit of Islet Transplant Objects (SUITO), Transplant Estimated Function (TEF), Homeostasis Model Assessment (HOMA)2‐B%, C‐peptide/glucose ratio (CP/G), C‐peptide/glucose creatinine ratio (CP/GCr), and BETA‐2 score—were compared against commonly used 90‐minute mixed meal tolerance test (MMTT) serum glucose and beta score to assess which of them best recognizes the state of acceptable blood glucose control without insulin supplementation after islet allotransplantation (ITx). We also tested whether the indices could identify the success of ITx based on the Igls classification of beta cell graft function. We analyzed values from 47 MMTT tests in 4 patients with up to 140 months follow‐up and from 54 MMTT tests in 13 patients with up to 42 months follow‐up. SUITO, CP/G, HOMA2‐B%, and BETA‐2 correlated well with the 90‐minute glucose of the MMTT and beta‐score (r 0.54‐0.76), whereas CP/GCr showed a modest performance (r 0.41‐0.52) while TEF showed little correlation. BETA‐2 and SUITO were the best identifiers and predictors of the need for insulin support, glucose intolerance, and ITx success ( P < .001), while HOMA2‐B% and TEF were unreliable. Single fasting blood sample SUITO and BETA‐2 scores are very practical alternative tools that allow for frequent assessments of graft function. Abstract : Out of six indices designed to assess beta cell function based on a single fasting blood sample after islet allotransplantation, SUITO and BETA‐2 are best able to recognize early islet dysfunction and the need for insulin supplementation.